RESULTS OF THE STUDY OF THE ETHNIC IDENTITY OF SOUTH OSSETIANS - A. B. Gagloeva (Вестник университета)
The article is devoted to the analysis of the results of the study of the ethnic identity of South Ossetians who have the citizenship of the Republic of South Ossetia and dual citizenship (the Republic of Southt Ossetia and the Russian Federation). It has been shown that the respondents’ ethnic identity is relevant and significant, which is accompanied by a positive value image of their ethnos and a positive attitude to its culture and history, which they try to preserve, traditions and norms of behavior adopted in it, as well as high satisfaction with membership in their ethno-cultural community with a pronounced need for identification with it and consolidation. The paper presents statistically reliable results of comparative analysis of indicators of ethnic identity of South Ossetians depending on citizenship: of the Republic of South Ossetia or dual (the Republic of South Ossetia and the Russian Federation).